Agrarian reforms in Interwar Europe - Morawski, Wojciech (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2019)
The agricultural reforms of the first half of the twentieth century were a side effect of the industrial revolution and demographic explosion. The variety of solutions used in individual countries reflected the complexity of local problems. In comparison, the communist reforms implemented after 1945 were dictated mainly by ideological considerations, and their aim was not so much to solve real problems as to break the will to resist and incapacitate entire societies.